2020
DOI: 10.1038/s41598-020-66914-w
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Perfusion Pressure and the Risk of Open-Angle Glaucoma: Systematic Review and Meta-analysis

Abstract: Low ocular perfusion pressure (opp) has been proposed as an important risk factor for glaucoma development and progression, but controversy still exists between studies. therefore, we conducted a systematic review and meta-analysis to analyze the association between opp and open-angle glaucoma (OAG). Studies were identified by searching PubMed and EMBASE databases. The pooled absolute and standardised mean difference in OPP between OAG patients and controls were evaluated using the random-effects model. Meta-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 73 publications
(27 reference statements)
1
21
0
1
Order By: Relevance
“…Such fluctuations also relate to changes in the ocular perfusion pressure in POAG ( 31 ), however, MAP variability can also affect the ocular perfusion pressure ( 7 ). Taking our findings into perspective, diurnal peaks in the intraocular pressure combined with diurnal MAP dips would likely result in repetitive drops in the ocular perfusion pressure ( 2 ), leading to glaucoma damage progression. On the other hand, as similarly reported in our study, glaucoma also relates to nocturnal hypotension ( 4 6 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Such fluctuations also relate to changes in the ocular perfusion pressure in POAG ( 31 ), however, MAP variability can also affect the ocular perfusion pressure ( 7 ). Taking our findings into perspective, diurnal peaks in the intraocular pressure combined with diurnal MAP dips would likely result in repetitive drops in the ocular perfusion pressure ( 2 ), leading to glaucoma damage progression. On the other hand, as similarly reported in our study, glaucoma also relates to nocturnal hypotension ( 4 6 ).…”
Section: Discussionmentioning
confidence: 89%
“…Open-angle glaucoma (OAG) is a progressive optic neuropathy characterized by loss of retinal ganglion cells and visual deterioration in eyes with or without high intraocular pressure (1). The pathogenesis of OAG is unclear but recent evidence focuses on risk factors that affect the ocular perfusion pressure (2,3), with nocturnal hypotension being the most important systemic vascular risk factor (4)(5)(6). The most plausible hypothesis is that low mean arterial pressure (MAP) leads to reduced ocular perfusion pressure, promoting the loss of retinal ganglion cell death due to ischemia of the optic nerve head (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 44 full-text articles were reviewed for further assessment. Seventeen articles were excluded for various reasons, including not being the largest MA investigating a risk factor ( n = 10) [25-34], full text could not be retrieved ( n = 2) [35, 36], full text was not in English ( n = 1) [37], full text was about IOP not glaucoma ( n = 5) [38-42], and not being an MA ( n = 4) [43-46]. Finally, 22 full-text articles [40, 47-67] were reviewed for further assessment summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nicotinamide supplementation can improve inner retinal function in glaucoma patients [99]. About the influencing factors of the ocular, a study shows that low ocular perfusion pressure increases the risk of glaucoma [42].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found a consistent association of low perfusion pressure and POAG but not NTG [ 11 ], even though some large epidemiologic studies were excluded due to mode of data reporting. The Leuven Eye Study found higher mean OPP values in glaucoma patients in a cross-sectional design [ 12 ].…”
Section: Vascular Risk Factors From Cohort Studiesmentioning
confidence: 99%